(untitled) (Bangladesh Journal of Agricultural Research, 2010)
A study was conducted during Boro and T. Aman seasons of 2002 at Bangladesh Rice Research Institute (BRRI), Gazipur to see the relationship of SPAD (Soil plant analysis development) reading with chlorophyll and N contents of leaves and to determine the critical LCC value for rice crops. Hybrid varieties Sonarbangla-1 and BRRI hybrid dhan0l were used for both rice crops and BRRI dhan29 and BRRI dhan31 were used as checks for Boro and T. Aman crops, respectively. Sonarbangla-1, BRRI hybrid dhan0l and BRRI dhan29 had similar leaf chlorophyll contents in Boro season. The maximum chlorophyll content (1.6-1.8 mg/g leaf) was observed at 39-42 soil plant analysis development (SPAD) value. In T. Aman season, the inbred BRRI dhan3l showed lower amount of chlorophyll (1.2-1.4 mg/g leaf) at 39-42 SPAD value compared to the hybrids Sonarbangla-1 and BRRI hybrid dhan 0l. Seasonal variation in chlorophyll content between Sonarbangla-1 and BRRI hybrid dhan0l was not large. Relationship between SPAD value and chlorophyll content was very close (R2 =>0.8) at panicle initiation and flower initiation stages for all the varieties. Similar relationship was also observed in case of SPAD value and nitrogen content in leaves. The results indicated that the rice leaves showing higher SPAD readings (>35) had higher chlorophyll and nitrogen contents. The adjusted critical LCC values were 3.0 for Boro and 3.5 for T. Aman seasons for all rice varieties. Key Words: Chlorophyll; nitrogen. DOI: 10.3329/bjar.v34i4.5841 Bangladesh J. Agril. Res. 34(4) : 661-672, December 2009